Influence of Research Continuity on Physician-Scientists' Career Success. (16th November 2021) - Brownrout, Jenna; Norato, Gina; Bensken, Wyatt; Squirewell, Catherine; Gordon, Taylor; Heiss, John; Nath, Avindra; Khan, Omar I.
Abstract : Objective: To determine if maintaining continuity in research topic and method from early to late career yields a greater likelihood of physician-scientists' research career success; that is, achieving research independence and producing impactful publications. Methods: To explore the effect of maintaining continuity in research, 108 neurology residency graduates (2000–2010) from former medical scientist training programs at the highest National Institute of Neurological Disorders and Stroke– and NIH-funded institutions were identified. Through comparison of PhD dissertations with postgraduate work, research continuity was deemed present if there was evidence of continuity in research topic and method. With publicly available SCOPUS, PubMed, and NIH RePORT data, the correlation that degree of continuity had with h-indices, number of grants awarded, and R01 acquisition was examined. Results: Nearly half of the graduates were classified as noncontinuous (45%), fewer than a quarter as somewhat continuous (22%), and roughly a third as very continuous (32%). The data demonstrated that research continuity increased the ability to acquire a R01, with 83% of R01 or R21 recipients having very continuous research. Very continuous graduates also had higher median number of grants received (2 [interquartile range (IQR) 1–3]) and a higher median h-index (17 [IQR 10.5–20]) compared to the somewhat continuous and noncontinuous groups. Conclusions: This study highlights research continuity as an important and modifiable variable during the training period of physician-scientists and one that may improve their career success and promote greater retention within the workforce.